The Role Of The Teacher In Increasing Students' Reading Literacy Motivation In Mts Darun Nahwi Indramayu - Caniyah (Beginner: Journal of Teaching and Education Management, 2023)
The low motivation of students' reading literacy is one of the factors that causes student achievement to decline. This is possible because their curiosity about subjects is still low, external factors (friends, family, and the environment) do not support studying Islamic Cultural History subjects and so on. Meanwhile, learning achievement of Islamic Cultural History is influenced by several factors such as student learning activities, learning models used by teachers in teaching, students' ability to accept the lessons provided by teachers, student learning motivation and so on. The role of the teacher greatly influences the motivation of reading literacy for students in Islamic Culture history lessons. This research use desciptive qualitative approach. The purpose of this study is to find out how the role of the teacher in increasing the reading literacy motivation of students at MTS Darun Nahwi and how the teacher's role is in increasing students' reading literacy motivation in Islamic Cultural History lessons at MTS Darun Nahwi